2021
DOI: 10.36278/jeaht.24.2.84
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Characteristics of Indoor Radon Concentration in Water Curtain Cultivation Facilities

Abstract: The aim of this study was to investigate indoor radon concentration in the water curtain cultivation facilities located in the rural area of Sejong city during the winter season. The bedrock of the southern part of the city is mainly composed of granite rocks, which have been reported to retain higher radon content than sedimentary and metamorphic rocks. The measured indoor radon concentrations were very high in all the facilities partially exceeding the recommended values provided in the 「Indoor Air Quality C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Water curtain cultivation (WCC) facilities spray groundwater to form a water film on the inner houses for heat insulation in the winter season, which leads to an additional risk of radon in the groundwater being released into the air [ 10 , 11 ]. A case study showed that radon concentrations in three nearby WCC facilities reached a few thousand Bq/m 3 and varied greatly among the measuring sites [ 12 ]. The maximum values occurred at dawn and then decreased with increasing ventilation, similar to those in an ordinary greenhouse.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Water curtain cultivation (WCC) facilities spray groundwater to form a water film on the inner houses for heat insulation in the winter season, which leads to an additional risk of radon in the groundwater being released into the air [ 10 , 11 ]. A case study showed that radon concentrations in three nearby WCC facilities reached a few thousand Bq/m 3 and varied greatly among the measuring sites [ 12 ]. The maximum values occurred at dawn and then decreased with increasing ventilation, similar to those in an ordinary greenhouse.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum values occurred at dawn and then decreased with increasing ventilation, similar to those in an ordinary greenhouse. However, the origin and detailed dynamics of radon accumulation have not been specified because of a lack of other information [ 12 ].…”
Section: Introductionmentioning
confidence: 99%